2011
DOI: 10.1007/978-3-642-19530-3_11
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Long-Term Ageing on Speaker Verification

Abstract: Abstract. The changes that occur in the human voice due to ageing have been well documented. The impact of these changes on speaker verification is less clear. In this work, we examine the effect of long-term vocal ageing on a speaker verification system. On a cohort of 13 adult speakers, using a conventional GMM-UBM system, we carry out longitudinal testing of each speaker across a time span of 30-40 years. We uncover a progressive degradation in verification score as the time span between the training and te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 21 publications
2
12
0
Order By: Relevance
“…This has been observed in [14], and a similar trend has been observed in the domain of face ageing [7]. The LLR scores of the imposters experience less change over time.…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…This has been observed in [14], and a similar trend has been observed in the domain of face ageing [7]. The LLR scores of the imposters experience less change over time.…”
Section: Resultssupporting
confidence: 56%
“…It was concluded that over a time interval of this length, variability in genuine speaker scores is more attributable to inter-session variability than to ageing. Our previous work [14] analysed longitudinal speaker data over a 30-40 year period. Using a Gaussian Mixture Model -Universal Background Model (GMM-UBM) system, the log likelihood ratio (LLR) scores of the speakers' recordings against their models were presented as a function of time span between training and testing.…”
Section: Introductionmentioning
confidence: 99%
“…From the score domain, researchers observed that verification scores of true speakers decreased progressively as the time span between enrollment and verification increased, while impostor scores were less affected [85,86]. Thus a stacked classifier method with an ageing-dependent decision boundary was applied to improve long-term verification accuracy.…”
Section: E Agingmentioning
confidence: 99%
“…A few studies have investigated the impact of voice ageing to speaker recognition accuracy [7], as well as considering the speaker's age as a factor affecting system performance evaluation [8,9]. In [7], the impact of long-term ageing on the performance of two automatic speaker verification systems (ASV) was evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have investigated the impact of voice ageing to speaker recognition accuracy [7], as well as considering the speaker's age as a factor affecting system performance evaluation [8,9]. In [7], the impact of long-term ageing on the performance of two automatic speaker verification systems (ASV) was evaluated. It was reported that age difference between enrollment and test samples increased equal error rate (EER) in the case of male speakers from 4.61%, when the difference was less than a year, to 32.74% when the age difference range was 51-60 years.…”
Section: Introductionmentioning
confidence: 99%